2020
DOI: 10.1111/joes.12396
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Environmental Consequences: A Review of the Empirical Literature

Abstract: As a key concern for human survival and development, environmental issues have been widely perceived to be impacted by various political institutional factors. A considerable body of literature has attempted to investigate how different political factors affect environmental policymaking and outcomes. In this paper, we critically review related scholarly works published in peer‐reviewed economic journals in the past 30 years, with an emphasis on the empirical literature. Political institutional factors conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 152 publications
(254 reference statements)
0
11
0
Order By: Relevance
“…Existing research has investigated many environmental outcomes, including environmental performance and policymaking [ 3 ], environmental enforcement [ 29 ], local firm behaviors [ 60 ], the interaction with other factors [ 61 ], and some policy instruments for central government inspection [ 62 ]. Many researchers have debated the causal relationship and realized that the trade−off or supplementary policy is essential [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has investigated many environmental outcomes, including environmental performance and policymaking [ 3 ], environmental enforcement [ 29 ], local firm behaviors [ 60 ], the interaction with other factors [ 61 ], and some policy instruments for central government inspection [ 62 ]. Many researchers have debated the causal relationship and realized that the trade−off or supplementary policy is essential [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sum, despite two controversial studies where both have the theoretical framework and empirical proof, there is not enough evidence on how decentralization affects environmental quality. Firstly, it is not easy to have a causal interpretation since decentralization or centralization usually coexist with some exogenous variation [ 39 ]. Secondly, two contrary findings indicated that some assuming condition is crucial [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results are robust to controlling for risk exposure, the capacity of the health care sector, legal origins, colonial history, and institutional quality. While the literature has previously discussed the relationship between democracy, political institutions, and environmental quality and policy (e.g., Folke 2014; Kammerlander and Schulze 2020; Ang and Fredriksson 2021;Hu and Chen 2021), to our knowledge the questions addressed in the present paper are novel. We believe our findings broaden our understanding of the environmental (and health) effects of government policymaking, in particular during a crisis situation.…”
Section: Introductionmentioning
confidence: 94%
“…In this regard, it seems that the level of corruption is the common denominator of environmental studies, therefore making it one of the main examples of an institutional obstacle to the evolution of sustainable development. However, it seems that the question of how governance quality influences the overall bioeconomic sphere remains understudied, thus deserving more attention (see, e.g., [ 57 , 58 ]). Against this background, by incorporating the neo-institutional approach, our work seeks to contribute to the fact-finding related to the impact of the quality of informal institutions on the dynamics of bioeconomy added value.…”
Section: Literature Reviewmentioning
confidence: 99%